Staging and Grading of Periodontitis in Relation to Hypertension: A Retrospective Study in Indonesia - Herlis Rahdewati; Dewi Ayuningtyas; Dimas Ilham Hutomo; Zahrani Rahma Lukman; Fatimah Maria Tadjoedin (Journal of Indonesian Dental Association, 2025)
Introduction – Pendahuluan: Hypertension (HT), a leading cause of cardiovascular morbidity and mortality, affects a significant portion of the global population and is a major public health concern. Periodontitis is a multifactorial chronic inflammatory disease involving tooth-supporting structures Objective – Tujuan: This study aims to evaluate the relationship between the severity of periodontitis and the prevalence of hypertension in an adult population. Methods – Metode: A retrospective cross-sectional study from medical records was conducted in this study. Data taken from medical records were age, gender, blood pressure, bleeding on probing, anti-hypertension drugs consumed by the patient, periodontitis diagnosis based on the 2017 classification, and history of other systemic diseases. This study involved 144 adult patients diagnosed with periodontitis, classified by staging (I-IV) and grading (A-C) Results – Hasil: Hypertension's impact on periodontitis severity becomes more evident with advancing age. HT group exhibited a higher prevalence of severe periodontitis (Stages III and IV) compared to normotensive patients (p=0.000), particularly among older age groups (45-60 years (p=0.029) and >60 years (p=0.038)). HT groups are more likely to exhibit Grade C periodontitis(p=0.04). HT patients demonstrate worse periodontal parameters that could contribute to accelerated disease progression and more severe outcomes. Conclusion – Kesimpulan: There is an association between the staging and grading of periodontitis and hypertension. These findings underscore the importance of a multidisciplinary approach in the management of periodontal and cardiovascular health to improve overall health outcomes. Keywords – Kata Kunci: Periodontitis, blood pressure, hypertension.